Teknologi Tepat Guna Mesin Pemeras Santan untuk UMKM Es Puter Kelurahan Ngaglik Kota Batu - Hadi, Yuswono; Purnomo, Purnomo; Taneo, Stefanus Yufra Menahen (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2022)
This community service held at Es Puter Manufacturer Community at Kota Batu. Several activities aimed to increase production capacity and then revenue. Coconut oil extraction process is the most critical process, the longest process and determines the quality of the product. After using Coconut Oil Extractor machine, production capacity and revenue increase at least 100 %.